The controversy around the conservation value of captive-bred lions - Potgieter, Pieter JJS, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
The conservation value of captive-bred lions is seriously questioned by most conservation minded people - to such an extent that they refuse to admit that these lions can make an enormous contribution towards the enhancement of the lion in the wild. Reasons offered range from alleged genetic contamination to captive-bred lions' alleged inability to adapt to conditions in the wild, including their alleged inability to acquire the social skills to function successfully in a pride. These allegations seem to be inspired by either a lack of understanding of the realities driving the decline of lion populations in Africa or a misunderstanding of the objectives and intentions of the captive-bred lion industry of South Africa or both. Notwithstanding unethical conduct and practices by lion farmers uncovered from time to time the industry at large is functioning on the principle of sustainable use. It exploits, by consumptive as well as non-consumptive use, a very esteemed and iconic game species economically, thereby generating a livelihood for self and for local communities. However, the industry is acutely aware of its responsibility to contribute to the survival and welfare of the lions in the wild. This responsibility is operationalised through various projects, including scientific research, financial support for lion conservation and, ultimately, there-establishment of lions in areas in Africa where they have become extinct.
The controversy surrounding the conservation value of captive-bred lions
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.